(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Linda TM, Febriarti BL, Zul D, Sofyanti N, Berlyansah A, Delfira N, Devi S. 2023. Isolation and characterization of endophytic bacteria from sterile leaf of Acrostichum aureum from Bengkalis Island (Riau, Indonesia) and its potency for antidiabetic. Biodiversitas 24: 1580-1588. Endophytic bacteria are found in symbiotic plant tissues. These bacteria pose potential sources for the natural product due to their health benefit, e.g., for antidiabetic activity. The present study aimed to isolate and characterize endophytic bacteria isolates from the sterile leaf of sea fern (Acrostichum aureum Linn.) from Bengkalis Island (Riau Province), Indonesia. Furthermore, to investigate their potency as an antidiabetic agent. The characteristics of isolates bacteria were described based on colony morphology and biochemical tests. A total of six endophytic bacteria were isolated from the sterile leaf of Acrostichum aureum. Their characteristics vary in shape, color, and size. The phytochemical screening indicated the presence of alkaloids and saponin in all the isolates. The results exhibited that the extract of the sterile leaf of A. aureum also gave a similar phytochemical compound of isolate endophytic bacteria. The dendrogram constructed from morphological and biochemical characteristics showed the separation of D.SB 4.2 from other six bacteria strains due to the positive antibacterial activity for Escherichia coli ATCC35218, Staphylococcus aureus ATCC29213, Salmonella typhi ATCC14028, and Bacillus subtilis ATCC11774. Out of six isolates, only isolate D.SB 5.2 was selected for the antidiabetic test. The isolates showed positive results on the activity as a-amylase inhibitor (18.12%). This study provides important information on endophytic bacteria isolates on A. aureum and their potency for antidiabetic agents.